Media dan Pendidikan Politik oleh Badan Pengawas Pemilu - Muhamad Fiqri Berlian; Ronni Juwandi; Febrian Alwan Bahrudin (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This study aims to look at the use of media by the Election Supervisory Board (Bawaslu) of Serang City as a form of political education. The media used are digital and conventional. Both can be maximized in the political education carried out by this organization. The focus of this research is related to the development of digitization of information dealing with community activities on social media so that information mobilization occurs as a campaign tool and political education. The supervisory role carried out by the Serang City Bawaslu in realizing honest, fair and democratic elections can keep up with the times, especially regarding prosecution of election violations. The method used in this research is descriptive qualitative method. Data collection was carried out by observation, interview and documentation techniques. The findings from this study are that there are obstacles from the community who are still not enthusiastic about responding to political education conducted by Bawaslu.